1994
DOI: 10.1002/j.1460-2075.1994.tb06810.x
|View full text |Cite
|
Sign up to set email alerts
|

EBNA-1, the major nuclear antigen of Epstein-Barr virus, resembles ‘RGG’ RNA binding proteins.

Abstract: Nuclear antigen 1 (EBNA‐1) is one of the key functions of the oncogenic DNA virus, Epstein‐Barr virus (EBV), and is the only viral protein consistently expressed in EBV‐associated malignancies. EBNA‐1 binds in a site‐specific manner to the viral DNA and is essential for viral replication, as well as for maintaining the genome as an extrachromosomal episome within infected cells. EBNA‐1 is not recognized by the cellular immune system. Here we demonstrate that, in addition to its known DNA binding properties, EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 61 publications
0
65
0
Order By: Relevance
“…The exosomal messenger pathway of cellular stress and infection may be an evolutionarily conserved protective mechanism that may cause disease if not properly regulated. EBERs can bind to viral (EBNA1) (48) and host RNA binding proteins (49). EBER1 and EBER2 associate with La, an abundant RNP in the nucleus of latently infected B cells (50) that binds nascent Pol III transcripts, protecting 3′ ends from exonucleases (51).…”
Section: Discussionmentioning
confidence: 99%
“…The exosomal messenger pathway of cellular stress and infection may be an evolutionarily conserved protective mechanism that may cause disease if not properly regulated. EBERs can bind to viral (EBNA1) (48) and host RNA binding proteins (49). EBER1 and EBER2 associate with La, an abundant RNP in the nucleus of latently infected B cells (50) that binds nascent Pol III transcripts, protecting 3′ ends from exonucleases (51).…”
Section: Discussionmentioning
confidence: 99%
“…Distinct functional domains have been mapped for DNA binding, dimerization (Chen et al, 1993(Chen et al, , 1994, DNA looping (Frappier & O'Donnell, 1994), RNA binding (Snudden et al, 1994) and transactivation (Ambinder et al, 1991). The observation of high heterogeneity of the EBNA-1 gene was unexpected and believed to be important for EBV, since Arrand et al (1989) reported that the overall homology at the nucleotide level across the EcoRI J regions of multiple EBV strains was 99 %, and the slight variation was mainly concentrated in noncoding regions.…”
Section: Discussionmentioning
confidence: 99%
“…The predicted amino acid sequence of EBNA-1, which consists of 641 amino acids (aa), can be separated into unique N-and C-terminal domains joined by internal, glycine\alanine-rich short repeat sequences (Baer et al, 1984). Several studies have been carried out to map functional domains within EBNA-1, including dimerization, transactivation, nuclear localization, DNA looping and RNA binding (Ambinder et al, 1991 ;Chen et al, 1993 ;Frappier & O'Donnell, 1994 ;Snudden et al, 1994 ;Yates & Camiolo, 1988). Most of the domains associated with these activities were localized to the C terminus of EBNA-1, except for RNA binding, which involved the RGG motifs at aa 34-55, 330-349 and 355-376 (Snudden et al, 1994 ;Fig.…”
Section: Introductionmentioning
confidence: 99%
“…144,145 This imposes risks related to immunogenic and transforming properties of EBNA1. [146][147][148] Another concern is that EBV-based vectors, although they have a prolonged retention even without selection pressure, they are often lost from cells under nonselective conditions. 127,129,142,149,150 An additional drawback is that EBV-based vectors are able to replicate only in primates, eliminating the exploitation of rodent model systems for preclinical assessment.…”
Section: Genetic Modification Of Hscs With Nonviral Systems Ep Papapementioning
confidence: 99%